# x/3=y/6

## Simple and best practice solution for x/3=y/6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for x/3=y/6 equation:

x in (-oo:+oo)

x/3 = y/6 // - y/6

x/3-(y/6) = 0

1/3*x-1/6*y = 0 // + -1/6*y

1/3*x = -(-1/6*y) // : 1/3

x = (-(-1/6*y))/1/3

x = 1/2*y

x = 1/2*y

### See similar equations:

| -a^2-9a+2=0 | | x^2-16/3x-14 | | (3x+4)(x-7)=0 | | ((4y+1)/(y-2))-((y-2)/(y-2)) | | 5y+3+7x*x-2-x*x+y= | | 5x+65=90 | | -7=x/-2-1 | | (2x-5)(4x+1)=0 | | (-7x+1)(-3x+6)= | | 16.99-.86x=177.81 | | 4x-71=81+12x | | 4x+21=3x+36 | | 2(x-3)(x+8)=0 | | 2x^2-1=49 | | (18-2x)(15-2x)(42-x)=6160 | | 4x(x-2)(2x+3)=0 | | 1+3y=6y-1/5 | | T=L(5+RS) | | A=25m^2 | | 7-2(3x+5)=3 | | 4x=-31 | | 6x=71/2 | | 5-6d+2d=-17 | | 56-x^2=20 | | T=L(5+RS)forS | | 68/4 | | -3(-x^2+5)=39 | | d=a/25m^2 | | (x^4+x^2-6)/(x^2+3) | | 6s^2-52+1=0 | | b=8-6/4 | | -6f+10=-14 | | x+(x+11)+(3x-16)=730 | | 6x^2+21x=-15 | | 2x+12=14-7x+14 | | 6(3n+2)=9(7n+4)+2 | | 23+8g=-4.2 | | 1/2+21/2 | | 4x(3x+4)=3 | | f(x)=x-2 | | 12n=1722n | | 7c+14=16 | | 4y=300-x | | y=-[2x+3] | | p-(p+30)=6(p-5)+4p | | x^2+14x-196=0 | | -9(v-5)=9v-9 | | 19=x/3+8 | | -4.45= | | 8x^2=-18x-9 | | 4ln(x+5)-7lnx= | | x(4x-6)=(4x+7)(x-3) | | -1c-9=-5 | | 17+2.6d=30 | | 6x(2x-15)=162 | | graphy=x^2-7 | | (4y-3z)(y+6z)= | | 9(2n+1)=9(8n+9)+8 | | e^2x+1=42 | | 36x^2=120x-100 | | 8c-3=-12 | | 3(2b-5)+10=7b-12 | | 2x-1=35 | | 3x+x/3=5 | | 2/11+(-5/7) |